2016
DOI: 10.3389/fnins.2016.00400
|View full text |Cite
|
Sign up to set email alerts
|

Nucleus Accumbens Shell and mPFC but Not Insula Orexin-1 Receptors Promote Excessive Alcohol Drinking

Abstract: Addiction to alcohol remains a major social and economic problem, in part because of the high motivation for alcohol that humans exhibit and the hazardous binge intake this promotes. Orexin-1-type receptors (OX1Rs) promote reward intake under conditions of strong drives for reward, including excessive alcohol intake. While systemic modulation of OX1Rs can alter alcohol drinking, the brain regions that mediate this OX1R enhancement of excessive drinking remain unknown. Given the importance of the nucleus accumb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
69
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(80 citation statements)
references
References 89 publications
(149 reference statements)
8
69
3
Order By: Relevance
“…Further, OX1r antagonism/blockade reduced voluntary EtOH self-administration in rats selectively bred for high EtOH preference (Anderson et al, 2014 ) and EtOH binge-drinking in C57BL/6J mice (Anderson et al, 2014 ; Carvajal et al, 2015 ; Olney et al, 2015 ). Taking into account first, the particular function of OX1r within the medial NAcc Shell, a key region involved in EtOH consumption in both mice and rats (Lei et al, 2016 ), and second, previous literature showing a role for OX activity in high EtOH drinkers, additional studies combining regional OX molecular characterization with appetitive, rather than consummatory behavior testing, will help to understand how endophenotype differences in NAcc mRNA OXr expression links to potential endophenotype differences in EtOH seeking.…”
Section: Discussionmentioning
confidence: 99%
“…Further, OX1r antagonism/blockade reduced voluntary EtOH self-administration in rats selectively bred for high EtOH preference (Anderson et al, 2014 ) and EtOH binge-drinking in C57BL/6J mice (Anderson et al, 2014 ; Carvajal et al, 2015 ; Olney et al, 2015 ). Taking into account first, the particular function of OX1r within the medial NAcc Shell, a key region involved in EtOH consumption in both mice and rats (Lei et al, 2016 ), and second, previous literature showing a role for OX activity in high EtOH drinkers, additional studies combining regional OX molecular characterization with appetitive, rather than consummatory behavior testing, will help to understand how endophenotype differences in NAcc mRNA OXr expression links to potential endophenotype differences in EtOH seeking.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism by which orexinergic innervation of NIC-activated regions of Acb affects NIC- related addictive behavior is not known. Previous studies have shown that orexinergic innervation of Acb could promote feeding, drinking [ 51 ] and drug intake [ 52 ]. Lei et al [ 52 ] have demonstrated that activation of orexin-1 receptors within Acb promotes alcohol intake in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that orexinergic innervation of Acb could promote feeding, drinking [ 51 ] and drug intake [ 52 ]. Lei et al [ 52 ] have demonstrated that activation of orexin-1 receptors within Acb promotes alcohol intake in mice. Others have reported that orexin-A in Acb is involved in feeding and drinking, but not alcohol preference [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The OX1R antagonists reduce drinking in the dark when injected into the nucleus accumbens shell, central nucleus of the amygdala, or ventral tegmental area (Lei et al, 2016; Olney, Navarro, & Thiele, 2017) and intermittent access alcohol drinking when injected into the medial prefrontal cortex, but not the anterior insular cortex and substantia nigra (Lei et al, 2016; Srinivasan et al, 2012) or the paraventricular thalamus (Barson et al, 2015). This is in contrast to the OX2R antagonist TCS OX2 29, which reduces two-bottle choice alcohol drinking when injected into the paraventricular thalamus where OX-B increases it to a greater extent than an equimolar dose of OX-A (Barson et al, 2015; Barson et al, 2017), but which has no effect on drinking in the dark when injected into the nucleus accumbens shell, central nucleus of the amygdala, or ventral tegmental area (Lei et al, 2016; Olney et al, 2017). This evidence supports the idea that alcohol drinking is stimulated by OX1R in multiple limbic brain regions, while OX2R is most active in the paraventricular thalamus where it specifically promotes high-level drinking.…”
Section: Role Of Orexin/hypocretin In Non-homeostatic Intakementioning
confidence: 99%
“…As with home-cage drinking, however, these receptor antagonists appear to exert their effects through different brain regions. This is suggested by the finding that operant self-administration of alcohol is reduced by injection of an OX1R antagonist into the shell of the nucleus accumbens (Lei et al, 2016) but by an OX2R antagonist in the core of the accumbens (Brown, Khoo, & Lawrence, 2013). …”
Section: Role Of Orexin/hypocretin In Non-homeostatic Intakementioning
confidence: 99%